Low-dose cadmium exposure promotes osteoclastogenesis by enhancing autophagy via inhibiting the mTOR/p70S6K1 signaling pathway. (15th August 2022) - Wang, Zhaojie; Li, Dongli; Mo, Lijun; Liang, Shujun; Liao, Xuemei; Guo, Sihui; Yang, Xingfen; Wei, Qinzhi
Abstract: Cadmium (Cd)-induced bone damage may be mediated through activating osteoclastogenesis. However, the underlying mechanism is unknown. The purpose of this study was to explore the effect and possible mechanism of CdCl2 -induced osteoclastogenesis in RAW264.7 cells. We found that a low concentration of CdCl2 (0.025 and 0.050 µM) did not affect the viability of RAW264.7 cells, but promoted osteoclastogenesis. A low concentration of CdCl2 increased the mRNA and protein expression of osteoclastogenesis-related genes. TRAP staining and transmission electron microscopy (TEM) also demonstrated that CdCl2 promoted osteoclastogenesis. A low concentration of CdCl2 upregulated the levels of LC3-II and Beclin-1, and decreased p62 expression. TEM showed relatively abundant autophagic vacuoles (autophagosomes) after CdCl2 exposure. A low concentration of CdCl2 downregulated the expression levels of Mtor and p70S6K1, and the relative protein expression ratios of p-mTOR/mTOR and p-p70S6K1/p70S6K1. When cells were treated with the autophagy inhibitor chloroquine (CQ) or mTOR activator MHY1485 combined with CdCl2, the expressions of osteoclastogenesis related-genes were decreased and autophagy was attenuated compared with cells treated with CdCl2 alone. Deficiencies in autophagosomes and osteoclasts were also observed. Taken together, the results indicate that a low concentration of CdCl2 promotes osteoclastogenesis by enhancing autophagy via inhibiting the mTOR/p70S6K1 signaling pathway. Highlights: CdCl2 promotes RANKL-induced osteoclastogenesis in RAW264.7 cells by enhancing autophagy. CdCl2 inhibites the activities of mTOR and p70S6K1 in RANKL-induced osteoclastogenesis of RAW264.7 cells. mTOR-mediated autophagy is involved in CdCl2 -induced osteoclastogenesis.